Property Taxes and Their Implications on the Real Estate Market: A Literature Review - Adil, Muhammad; Syafaruddin, Syafaruddin (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This research aims to provide a comprehensive overview of property taxes and their implications for the real estate market, covering economic, social, political, and environmental dimensions. Research Design and Methodology: The research methodology involved a systematic literature review that relied on insights from multiple disciplinary perspectives, including economics, public policy, urban planning and environmental studies. Findings and Discussion: The findings underscore the pivotal role of property taxes in shaping property values, investment decisions, and broader urban development patterns. Implications: Policymakers, practitioners, and researchers can utilize insights from this study to develop holistic strategies for property tax reform that promote fairness, transparency, and accountability in governance.